Colour mixing based on daylight - Meyn, Jan-Peter (European Journal of Physics, 2008)
Colour science is based on the sensation of monochromatic light. In contrast to that, surface colours are caused by reflection of wide sections of the daylight spectrum. Non-spectral colours like magenta and purple appear homologous to colours with spectral hue, if the approach of mixing monochromatic light is abandoned. It is shown that a large region of the colour space can be covered by mixing three primary colours derived from lossless spectral decomposition of daylight. These primaries are specified by hue, saturation and luminosity. Duality of additive and subtractive mixing is formulated quantitatively. Experimental demonstrations of calculated results are suggested. This paper is intended for undergraduate optics courses, and advanced interdisciplinary seminars on arts and physics. © 2008 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.PI.PDP.colour